Juvenile Dermatomyositis: A Case Report - Bhuiyan, Ishrat; Hossain, Md Shahadat; Akhter, Mafuza; Chowdhury, Shaheen Reza (Journal of Shaheed Suhrawardy Medical College, 2013)
Juvenile dermatomyositis is a chronic inflammatory multisystem disease that affects primarily the skin and muscle. A 5 years old girl presented with heliotrope rash, gottron's papules, and muscular weakness for one and half month. Other systemic examination revealed no abnormalities. Investigation reveals- Erythrocyte Sedimentation rate was raised, muscle enzymes were several fold elevated, skin biopsy consistent with dermatomyositis, EMG consistent with polymyositis. So confirmed diagnosis was made as Juvenile dermatomyositis (JDM). The patient was managed by systemic steroid and showed good response to treatment. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16225 J Shaheed Suhrawardy Med Coll, 2013;5(1):63-66